Progressive Hemodialysis: Is It The Future?. Issue 3 (15th November 2015) - Libetta, Carmelo; Nissani, Peni; Dal Canton, Antonio
Abstract: Progressive hemodialysis is based on the simple idea of adjusting its dose according to residual renal function (RRF). The progressive, infrequent paradigm is slowly gaining a foothold among nephrologists, despite a lot of skepticism in the scientific world. Given the importance of RRF preservation in conservative therapy, it seems a contradiction to ignore the contribution of RRF when patients initiate hemodialysis (HD), especially when it is routinely considered with peritoneal dialysis. While a three‐times‐weekly HD regimen is broadly considered the standard starting regimen for new patients, twice‐weekly HD has been used in selected patients and is currently a common practice in South‐East Asia. Small studies indicate that a once‐weekly HD regimen may be a viable starting option as well. Progressive hemodialysis still requires validation, yet it is promising. We share the belief that a randomized clinical trial to investigate progressive hemodialysis is much needed, but we also strongly recommend including a once‐weekly HD starting dose as part of any such investigation.